2007
DOI: 10.1177/1545968306294730
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Activation During Cognitive Control in Patients With Moderate to Severe Traumatic Brain Injury

Abstract: These findings suggest that neural networks mediating cognitive control are altered after moderate to severe TBI, possibly as a result of diffuse axonal injury, and that the typical relationship of brain activation to performance is disrupted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
81
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 39 publications
19
81
3
Order By: Relevance
“…Our findings are broadly consistent with other f MRI studies that observed altered, more extensive, neural activation patterns in patients with TBI (Christodoulou et al, 2001;McAllister et al, 1999McAllister et al, , 2001Newsome et al, 2007aNewsome et al, , 2007bPerlstein et al, 2004;Scheibel et al, 2003Scheibel et al, , 2007. For example, other studies also reported over-activation in regions mediating working memory (McAllister et al, 2001) or response inhibition (Scheibel et al, 2007) in adult patients with TBI.…”
Section: Neural Correlates Of Attention In Pediatric Tbi 429supporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are broadly consistent with other f MRI studies that observed altered, more extensive, neural activation patterns in patients with TBI (Christodoulou et al, 2001;McAllister et al, 1999McAllister et al, , 2001Newsome et al, 2007aNewsome et al, , 2007bPerlstein et al, 2004;Scheibel et al, 2003Scheibel et al, , 2007. For example, other studies also reported over-activation in regions mediating working memory (McAllister et al, 2001) or response inhibition (Scheibel et al, 2007) in adult patients with TBI.…”
Section: Neural Correlates Of Attention In Pediatric Tbi 429supporting
confidence: 92%
“…This literature suggests that adolescents and adults with ADHD show reduced or under-activation of relevant neural circuits (Epstein, in press;Rubia et al, 2005;Smith et al, 2006;Tamm et al, 2006). Our findings of over-activation in regions related to sustained attention align more closely with f MRI studies of adult TBI using working memory tasks (McAllister et al, 2001;Scheibel et al, 2007), and recent f MRI studies of children with TBI (Karunanayaka et al, 2007;Newsome et al, 2007b), suggesting that observed attentional deficits in pediatric TBI and ADHD may not share a common underlying neuropathology. Nevertheless, some children with TBI develop significant inattention problems post-injury, often termed secondary ADHD (SADHD) (Max et al, 2005b(Max et al, , 2005c).…”
Section: Neural Correlates Of Attention In Pediatric Tbi 429supporting
confidence: 82%
See 2 more Smart Citations
“…Such assessments are also taking advantage of computerized and virtual assessment techniques as well as the ability to automate the assessment (Cernich et al, 2007;Iverson et al, 2005;Schatz & Putz, 2006;Slobounov et al, 2006). Likewise, various cognitive neuroscience measures either by themselves or combined with functional neuroimaging methods hold great promise for more accurate assessment of the effects of TBI on behavior and cognition (Bergemalm & Lyxell, 2005;Casson et al, 2006;Chan, 2001;Chen et al, 2007;Cicerone et al, 2006;Dockree et al, 2006b;Jantzen et al, 2004;Mendez et al, 2005;O'Keeffe et al, 2007a;O'Keeffe et al, 2007b;Scheibel et al, 2007;Suh et al, 2006). These types of studies applied to PPCS will likely advance the field rather than another round of testing with traditional "clinical" neuropsychological measures (Heitger et al, 2004(Heitger et al, , 2005.…”
Section: Ecological Validity Of the Clinical Neuropsychological Approachmentioning
confidence: 99%